Structural and Kinetic Dissection of the endo‐α‐1, 2‐Mannanase Activity of Bacterial GH99 Glycoside Hydrolases from Bacteroides spp. Issue 5 (8th December 2014) - Hakki, Zalihe; Thompson, Andrew J.; Bellmaine, Stephanie; Speciale, Gaetano; Davies, Gideon J.; Williams, Spencer J.
Abstract Glycoside hydrolase family 99 (GH99) was created to categorize sequence‐related glycosidases possessing endo‐α‐mannosidase activity: the cleavage of mannosidic linkages within eukaryotic N‐glycan precursors (Glc1–3Man9GlcNAc2), releasing mono‐, di‐ and triglucosylated‐mannose (Glc1–3‐1, 3‐Man). GH99 family members have recently been implicated in the ability of Bacteroides spp., present within the gut microbiota, to metabolize fungal cell wall α‐mannans, releasing α‐1, 3‐mannobiose by hydrolysing αMan‐1, 3‐αMan→1, 2‐αMan‐1, 2‐αMan sequences within branches off the main α‐1, 6‐mannan backbone. We report the development of a series of substrates and inhibitors, which we use to kinetically and structurally characterise this novel endo‐α‐1, 2‐mannanase activity of bacterial GH99 enzymes from Bacteroides thetaiotaomicron and xylanisolvens. These data reveal an approximate 5 kJ mol−1 preference for mannose‐configured substrates in the −2 subsite (relative to glucose), which inspired the development of a new inhibitor, α‐mannopyranosyl‐1, 3‐isofagomine (ManIFG), the most potent (bacterial) GH99 inhibitor reported to date. X‐ray structures of ManIFG or a substrate in complex with wild‐type or inactive mutants, respectively, of B. xylanisolvens GH99 reveal the structural basis for binding to D‐mannose‐ rather than D‐glucose‐configured substrates.